Comparative Genomic Analysis of Soil Dwelling Bacteria Utilizing a Combinational Codon Usage and Molecular Phylogenetic Approach Accentuating on Key Housekeeping Genes - Saha, Jayanti; Saha, Barnan K.; Pal Sarkar, Monalisha; Roy, Vivek; Mandal, Parimal; Pal, Ayon (Frontiers in Microbiology, 2019)
Soil is a diversified and complex ecological niche, home to a myriad of microorganisms particularly bacteria. The physico-chemical complexities of soil results in a plethora of physiological variations to exist within the different types of soil dwelling bacteria, giving rise to a wide variation in genome structure and complexity. This serves as an attractive proposition to analyze and compare the genome of a large number soil bacteria to comprehend their genome complexity and evolution. In this study a combination of codon usage and molecular phylogenetics of the whole genome and key housekeeping genes like infB (translation initiation factor 2), trpB (tryptophan synthase, beta subunit), atpD (ATP synthase, beta subunit) and rpoB (RNA polymerase, beta subunit) of 92 soil bacterial species spread across the entire eubacterial domain and residing in different soil types was performed. The results indicated the direct relationship of genome size with codon bias and coding frequency in the studied bacteria. The codon usage profile demonstrated by the gene trpB was found to be relatively different from the rest of the housekeeping genes with a large number of bacteria having a greater percentage of genes with Nc values less than the Nc of trpB. The results from the overall codon usage bias profile also depicted that the codon usage bias in the key housekeeping genes of soil bacteria was majorly due to selectional pressure and not mutation. The analysis of hydrophobicity of the gene product encoded by the rpoB coding sequences demonstrated tight clustering across all the soil bacteria suggesting conservation of protein structure for maintenance of form and function. The phylogenetic affinities inferred using 16S rRNA gene and the housekeeping genes demonstrated conflicting signals with trpB gene being the noisiest one. The housekeeping gene atpD was found to depict the least amount of evolutionary change in the soil bacteria considered in this study except in two Clostridium species. The phylogenetic and codon usage analysis of the soil bacteria consistently demonstrated the relatedness of Azotobacter chroococcum with different species of the genus Pseudomonas.